Altered pain modulation to noxious heat thermal stimuli in burning mouth syndrome. (13th August 2020) - Nishihara, Chisa; Watanabe, Kosuke; Ozasa, Kana; Khan, Junad; Eliav, Eli; Imamura, Yoshiki; Noma, Noboru
Abstract: Objectives: The aim of this study was to examine temporal summation (TS) and conditioned pain modulation (CPM) in patients with burning mouth syndrome (BMS) and healthy controls using intra‐epidermal electrical stimulation (IES). Materials and Methods: Twenty‐six female patients with BMS and 27 healthy female controls participated in this study. A single stimulus with electrical stimulation followed by a train of 10 successive stimuli was administered to the right chin of participants in both the BMS and control groups. CPM was evaluated with the changes of TS calculated from the difference in numerical pain scale data between these two test stimuli and the following warm (40°C) and hot (47°C) conditioning stimuli applied at the non‐dominant hand in both the BMS and control groups. Results: TS was present in both the BMS and control groups. CPM in the BMS group was significantly less efficient at the 47°C condition than that in the control group, while no significant difference was observed in the CPM between the BMS and the control groups at the 40°C condition. Conclusion: These findings indicate that BMS is associated with a deficit inhibitory CPM and implicate the involvement of the central nervous system in the pathophysiology of BMS.